A new reading of the Physics teaching learning process in the initial formation of teachers, from the perspective of the education for the sustainability - Evora Larios, Onelia E. (Avances en Supervisión Educativa, 2016)
The accelerated scientific and technical progress, as well as its implication in all the spheres of the society, it forces to reorient the teaching of sciences in the scholastic institutions and to integrate to themes of the sustainable development. For this reason, the pedagogical sciences universities must incorporate these ideas in the process of formation by means of educational actions that allow students reach the professional competition necessary to be able to advance successfully in this direction. The article deals about a research in the initial formation of Physics teachers, in which a didactic strategy was developed with the objective to contribute to the environmental education for the sustainable development in the students.